2011
DOI: 10.1002/elsc.201000162
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state fermentation of lignocellulotic materials for the production of enzymes by the white‐rot fungus Trametes hirsuta in a modular bioreactor

Abstract: Trametes hirsuta, a filamentous basidiomycete, was successfully cultivated in solid‐state fermentation (SSF) on a mixture of pine wood chips and orange peel in a novel bioreactor that allows mixing of the inoculated solid material during the fermentation. Copper sulfate or xylidine (2,5‐dimethylaniline) were added to enhance the production of enzymes, especially laccases. For comparison, Trametes hirsuta was also cultivated in submerged conditions. The effect of additives in SSF was low, whereas the choice of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The MnP activities (47,300 nkat L -1 or 340 nkat g -1 DM) obtained in the present study are higher than those in other bioreactor cultivation experiments reported to date. Böhmer et al [48], however, reported higher laccase activities in SSC with Trametes hirsuta in a rotary drum bioreactor. Although Böhmer et al obtained high laccase activities, this activity was gained during 35 days of continuous cultivation, whereas in the present work, high laccase activities were obtained already after 8 days.…”
Section: Discussionmentioning
confidence: 96%
“…The MnP activities (47,300 nkat L -1 or 340 nkat g -1 DM) obtained in the present study are higher than those in other bioreactor cultivation experiments reported to date. Böhmer et al [48], however, reported higher laccase activities in SSC with Trametes hirsuta in a rotary drum bioreactor. Although Böhmer et al obtained high laccase activities, this activity was gained during 35 days of continuous cultivation, whereas in the present work, high laccase activities were obtained already after 8 days.…”
Section: Discussionmentioning
confidence: 96%
“…However, optimized cultivation and process conditions are required to produce sufficient quantities of material for these purposes. Solid state fermentation (SSF) involves growing microorganisms on a solid substrate with no free liquid (1)(2)(3)(4). It is very useful for basidiomycete cultivation because it simulates the conditions of their natural habitats and protects the filamentous mycelium against mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…This is largely due to the use of SmF for the production of penicillin after 1940 (5). However, there has recently been a resurgence of interest in SSF because of its potential applications in the food, feed, pharmaceutical and agricultural industries, as well as in the production of primary and secondary metabolites and the development of sustainable bioprocesses (1,4,6). 1 Institut f€ ur Lebensmittel-und Bioverfahrenstechnik, Technische Universit€ at Dresden, Dresden, Germany 2 Gesellschaft f€ ur Wissens-und Technologietransfer-TU Dresden GmbH, (GWT-TUD GmbH), Dresden, Germany…”
Section: Introductionmentioning
confidence: 99%
“…A couple of highlights out of the broad spectrum of inspiring talks are presented in this special issue. It includes contributions from numerous hot spots of German and Swiss bioprocess engineering groups in Aachen (Jochen Büchs) 1, Braunschweig (Ezequiel Franco‐Lara) 2, Hamburg (Reiner Luttmann) 3, Kaiserlautern (Ulber) 4, Munich (Dirk Weuster‐Botz and Thomas Becker) 5–7, Senftenberg (Klaus‐Peter Stahmann) 8, Wädenswil/Zurich (Dieter and Regine Eibl) 9 and Dresden with myself 10, 11. Additionally a technical report of one of the leading companies in the field of bioreactor development and production, Satorius Stedim, is included 11.…”
mentioning
confidence: 99%
“…However, because these fungi are not well understood and they are so heterogeneous, bioengineering for these processes is still needed. Two contributions in this issue show novel bioreactor design and developments in this field 8, 11. Further articles deal with monitoring and control strategies for economic and safe operation of new plants in biotechnology 6, 7.…”
mentioning
confidence: 99%